Respostas

A melhor resposta!
2014-04-25T21:02:16-03:00
7x-x²-6=0
x²-7x-6=0
Utilizaremos a equação de bhaskara -b+-√b²-.4.a.c /2a
-(-7)+-√7²-.4.1.-6
7+-√49-.(-24) /2
7+-√25/2
7+-5/2
x'=6
x"=1
1 5 1
2014-04-25T21:04:16-03:00
  7x-x²-6=0
-x²+7x-6=0⇒     a= -1       b= +7    c= -6                x'=-7+5  =    -2
                                                                              ¨¨¨¨¨¨¨¨      ¨¨¨¨  =  +1
Δ=b²-4.a.c                                                               2.(-1)       -2
Δ=(7)²-4.(-1).(-6)
Δ=49-24                                                               x"=-7-5 =  -12
Δ=25    ⇒raiz de 25 é 5                                            ¨¨¨¨¨¨¨¨   ¨¨¨¨¨¨ =    +6
                                                                                2.(-1)     -2
1 2 1